NOMINAL STYLE IN THE MODERN GERMAN LANGUAGE - Abdulrahimova, G.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
This article addresses the issue of nominal style in modern German. The process of using nominal constructions, which is associated with the phenomenon of language saving, is analyzed. Too long sentences and constructions are difficult for language perception. The nominal style arose under the influence of the development of technology and science, where brevity and accuracy are important. In connection with the current tendency to nominalize sentences in modern German, combinatorics within nominee groups is of considerable interest. Nominal constructions can be used both in written and in oral speech. According to the author, the trend towards nominalization can be observed at present at almost all levels of language use. The author pays the main attention in the work to the fact that with the help of this tendency we can actually spend less time in conversation. The article also reflected various ideas of linguists on the nominal nature of sentences in both written and spoken language, in modern German.